2004
DOI: 10.1200/jco.2004.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Deleted in Colon Cancer Protein Expression in Colorectal Cancer Metastases: A Major Predictor of Survival in Patients With Unresectable Metastatic Disease Receiving Palliative Fluorouracil-Based Chemotherapy

Abstract: Our results indicate that expression of the DCC protein in CRC metastases is similar to that observed in the corresponding primary tumors and represents a dominant predictor of survival in patients with unresectable, advanced CRC who are undergoing palliative FU-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
12
0
4
Order By: Relevance
“…The gene DCC , which maps to 18q21, is recognised as a key player in colorectal carcinogenesis and is the primary candidate for the biological effect of chromosome 18q allelic imbalance. Patients with locally advanced stage II or stage III disease appear to demonstrate a significantly poorer prognosis with loss of 18q 5558…”
Section: Molecular Prognostic Factorsmentioning
confidence: 99%
“…The gene DCC , which maps to 18q21, is recognised as a key player in colorectal carcinogenesis and is the primary candidate for the biological effect of chromosome 18q allelic imbalance. Patients with locally advanced stage II or stage III disease appear to demonstrate a significantly poorer prognosis with loss of 18q 5558…”
Section: Molecular Prognostic Factorsmentioning
confidence: 99%
“…Various studies reported that DCC is a predictor of distant metastasis and prognosis in colorectal cancer (24)(25)(26). Furthermore, DCC expression has been shown recently to predict clinical outcome to fluorouracilbased chemotherapy (27). Other studies have reported that the DCC gene product induced apoptosis through a caspasedependent mechanism (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Pada tahun 1990, Fearon dan Vogelstein, seperti dikutip oleh Kelli 2 yang sudah memperkenalkan patogenesis karsinoma kolorektal dan dinyatakan bahwa paling tidak ditemukan 5 mutasi gen. Secara histopatologi melalui pemeriksaan imunohistokimia, mutasi gen yang berperan dalam keganasan kolorektal dapat diketahui dengan cara melihat ekspresi proteinnya. [10][11][12] Meskipun ini sebagai kasus multifaktorial dapat ditinjau dari biologi molekuler keganasan kolorektal ini terjadi akibat mutasi beberapa gen seperti gen APC, K-ras, DCC, dan p53. [3][4][5] Progresivitas dan kemungkinan penyebaran keganasan kolorektal ditentukan oleh adhesi antarselnya.…”
Section: Pendahuluanunclassified
“…Penelitian lain pernah melaporkan tidak terdapat ekspresi protein tersebut berhubungan dengan respons pemberian kemoterapi. 10,12,14 Empat kasus keganasan kolorektal pada usia <40 tahun hanya didapatkan salah satu ekspresi protein gen supresor tumor (ekspresi protein DCC positif dan ekspresi protein p53 negatif atau sebaliknya). Meskipun dilakukan penelitian pada stadium yang sama (stadium III), ternyata masih mungkin didapatkan variasi hasil pemeriksaan imunohistokimia ekspresi protein tersebut pada setiap subjek yang diteliti.…”
Section: Pembahasanunclassified
See 1 more Smart Citation